Integral de 1/(e^(x/4)+4e^(-x/4)) dx
Solución
Respuesta (Indefinida)
[src]
/ x\
/ | -|
| | 4|
| 1 |e |
| ----------- dx = C + 2*atan|--|
| x -x \2 /
| - ---
| 4 4
| E + 4*E
|
/
∫4e4(−1)x+e4x1dx=C+2atan(2e4x)
/ 2 / 2 \\ / 2 \
- RootSum|z + 1, i -> i*log|----- + 2*i|| + RootSum\z + 1, i -> i*log(2 + 2*i)/
| |3 ___ ||
\ \\/ x //
RootSum(z2+1,(i↦ilog(2i+2)))−RootSum(z2+1,(i↦ilog(2i+3x2)))
=
/ 2 / 2 \\ / 2 \
- RootSum|z + 1, i -> i*log|----- + 2*i|| + RootSum\z + 1, i -> i*log(2 + 2*i)/
| |3 ___ ||
\ \\/ x //
RootSum(z2+1,(i↦ilog(2i+2)))−RootSum(z2+1,(i↦ilog(2i+3x2)))
-RootSum(_z^2 + 1, Lambda(_i, _i*log(2/x^(1/3) + 2*_i))) + RootSum(_z^2 + 1, Lambda(_i, _i*log(2 + 2*_i)))
Estos ejemplos se pueden aplicar para introducción de los límites de integración inferior y superior.